Study on Environmental Effects Induced by Quasirectangle Shield Tunnelling with Analytical Stiffness Matrix - Jianguo Xu; Fengyang Miao; Lei Kou; Jinpeng Zhang (Advances in Civil Engineering)
During the quasirectangle shield tunnelling, the soil around the tunnel is inevitably disturbed which results in different degrees of additional stresses and displacement of the soil. In this paper, the environmental effects caused by the construction of quasirectangle shield are analyzed by the analytical stiffness matrix method, focusing on the law of the additional stress field and the deformation of the multilayered soil induced by the construction of a quasirectangle shield. The results show that the additional stresses field has localized characteristics around the quasirectangle shield. The further away from the excavation face, the smaller the stress is. Also, shell friction and synchronous grouting pressure have a significantly greater influence on the additional stress field. Finally, the horizontal settlement groove of the quasirectangle shield is roughly symmetrical and parabolic along the tunnel axis, with a groove width range of about 20m. Synchronous grouting pressure has a greater effect on longitudinal ground deformation.